Antimicrobial resistance of Salmonella spp. in swine: Review - Lantmann, Thiago Langer (2022)
Swine farming represents a very relevant activity for Brazil, generating jobs, income and development. Currently, the national and international market has been demanding an increasingly qualified herd health status. Within this, salmonellosis is a disease that deserves to be highlighted. Salmonella is an etiological agent of great involvement in food outbreaks in humans, and has shown an elevated increase in antimicrobial resistance due to the indiscriminate use of antibiotics in treating livestock and humans, becoming a global threat to public health. The emergence of isolation of Salmonella with such resistance has been described in humans, food and animals for consumption. For this reason, this paper conducted a literature review on Salmonella spp. and its resistance to the use of antibiotic therapy in swine farming, with consultation of normative instructions, dissertations, and scientific articles from several databases such as Scielo, ScienceDirect, and PubMed. It was possible to verify the great antimicrobial resistance of Salmonella against the countless active principles used in antibiotic therapy in swine farming over the years. It was also found that for the upcoming years there is a trend in using alternatives to antibiotics, such as essential oils, organic and inorganic acids, among others.